2022
DOI: 10.1021/acs.jpclett.2c03161
|View full text |Cite
|
Sign up to set email alerts
|

Mapping H+ in the Nanoscale (A2C4)2-Ag8 Fluorophore

Abstract: When strands of DNA encapsulate silver clusters, supramolecular optical chromophores develop. However, how a particular structure endows a specific spectrum remains poorly understood. Here, we used neutron diffraction to map protonation in (A2C4)2-Ag8, a green-emitting fluorophore with a “Big Dipper” arrangement of silvers. The DNA host has two substructures with distinct protonation patterns. Three cytosines from each strand collectively chelate handle-like array of three silvers, and calorimetry studies sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…This interesting phenomenon is not yet fully understood, but it has been reported that it could be due to a perturbation of silver on the charge distribution (shifting of pK a values) of the nucleobases. 37 Similar to how metal cations induce deprotonation of guanine at the N1 position in ribozymes, 38 silver could cause acidification of the NH groups of G 9 , suggesting that there are different microenvironments inside [(DNA) 2 −Ag 16 Cl 2 ] 10-. Bader charges for silver atoms interacting with N7(G 7 ) and N1(G 9 -) are similar (0.393 and 0.383 |e| vs 0.377 and 0.369 |e|, respectively; Figure S1), but the environment of G 7 and G 9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interesting phenomenon is not yet fully understood, but it has been reported that it could be due to a perturbation of silver on the charge distribution (shifting of pK a values) of the nucleobases. 37 Similar to how metal cations induce deprotonation of guanine at the N1 position in ribozymes, 38 silver could cause acidification of the NH groups of G 9 , suggesting that there are different microenvironments inside [(DNA) 2 −Ag 16 Cl 2 ] 10-. Bader charges for silver atoms interacting with N7(G 7 ) and N1(G 9 -) are similar (0.393 and 0.383 |e| vs 0.377 and 0.369 |e|, respectively; Figure S1), but the environment of G 7 and G 9…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between neutral guanine and silver cations through the N7 atom and the neighboring carbonyl group (C6 position) has been documented in the literature to be the most stable position for the metallobase pair. , However, different protonation states of the same nucleobase can coexist within the same metal–DNA complex. This interesting phenomenon is not yet fully understood, but it has been reported that it could be due to a perturbation of silver on the charge distribution (shifting of p K a values) of the nucleobases . Similar to how metal cations induce deprotonation of guanine at the N1 position in ribozymes, silver could cause acidification of the NH groups of G 9 , suggesting that there are different microenvironments inside [(DNA) 2 –Ag 16 Cl 2 ] 10‑ .…”
Section: Resultsmentioning
confidence: 99%
“…This halide binds Ag + ∼ 10 10 times stronger than DNA, as evident in the optical and mass spectra. 66,67 When 2 I − :DNA are added, the absorption feature at λ abs ≲ 430 nm due to AgI(s) emerges, establishing that silvers are stripped from DNA (Figure S7A). 68 I − targets and eliminates Ag + from the larger clusters to favor the smallest Ag 6 4+ cluster, but the larger clusters reassemble when the precipitated Ag + is replaced (Figure 4).…”
Section: +mentioning
confidence: 98%
“…This interesting phenomenon is not yet fully understood but it has been reported that it could be due to a perturbation of silver on the charge distribution (shifting of pK a values) of the nucleobases. 26 Similar to how metal cations induce deprotonation of guanine at N1 position in ribozymes, 27 silver could cause acidification of the NH groups of G 9 , suggesting that there are different microenvironments inside [(DNA) 2 -Ag 16 Cl 2 ] 10-. Bader charges for silver atoms interacting with N7(G 7 ) and N1(G 9 -) are similar (0.393 and 0.383 |e| vs. 0.377 and 0.369 |e|, respectively; Figure S1) but the environment of G 7 and G 9is different in terms of hydrogen bonds contribution and pi-stacking interactions established with their neighboring bases.…”
Section: Toc Graphicmentioning
confidence: 99%